Concussion in European professional football: a view of team physicians - Gouttebarge, V.; Ahmad, I.; Iqbal, Z.; Orhant, E.; Rosenbloom, C.; Sas, K.; Kerkhoffs, G. M. M. J. (BMJ Open Sport & Exercise Medicine, 2021)
Objectives The objective was to explore the view and thoughts of physicians working in professional football about several aspects (eg, education and use of video footages) likely to enhance concussions` recognition and on-field management.